THE FACTORS THAT INFLUENCE THE ACADEMIC PERFORMANCE OF EFL STUDENTS AT UNDERGRADUATE LEVEL OF PRIVATE UNIVERSITIES AT DUBAI AND SHARJAH IN THE UNITED ARAB EMIRATES - Salameh, Walid (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
This study seeks to determine the Factors that Influence Academic Performance of EFL students at Undergraduate Level at Private Universities at Dubai and Sharjah in the United Arab Emirates. It is the first study of its kind relating to the performance of student of undergraduates students at Canadian University Dubai. Besides it would be relevant to point out the facts that are related to the performance of undergraduate students. The research method in terms of achieving the objectives of this study is a qualitative form of research. The Data collection method will be questionnaire guide, the questionnaire guide will be administer to the key respondents who are of interest to make this studies meets the objective.